A review of the occurrence and causes for wildfires and their impacts on the geoenvironment - O'Kelly, Brendan (My University, 2024)
Wildfires have short- and long-term impacts on the geoenvironment, including the changes to biogeochemical and mechanical properties of soils, landfill stability, surface- and groundwater, air pollution, and vegetation. Climate change has increased the extent and severity of wildfires across the world. Simultaneously, anthropogenic activities — through the expansion of urban areas into wildlands, abandonment of rural practices, and accidental or intentional fire-inception activities — are also responsible for a majority of fires. This paper provides an overall review and critical appraisal of existing knowledge about processes induced by wildfires and their impact on the geoenvironment. Burning of vegetation leads to loss of root reinforcement and changes in soil hydromechanical properties. Also, depending on the fire temperature, soil can be rendered hydrophobic or hydrophilic and compromise soil nutrition levels, hinder revegetation, and, in turn, increase post-fire erosion and the debris flow susceptibility of hillslopes. In addition to direct hazards, wildfires pollute air and soil with smoke and fire suppression agents releasing toxic, persistent, and relatively mobile contaminants into the geoenvironment. Nevertheless, the mitigation of wildfires’ geoenvironmental impacts does not fit within the scope of this paper. In the end, and in no exhaustive way, some of the areas requiring future research are highlighted.
PUBLISHED
Keywords: Smart & Sustainable Planet; Climate Change; Climate Change Impacts on the Environment; ENVIRONMENTAL ENGINEERING; Environmental Change; Environmental Engineering, Pollution Control; Environmental Geotechnics; Geoenvironmental engineering; Natural Hazards; Soil Mechanics; fires; soil and groundwater conditions; wildfires